Extrapulmonary tuberculosis, human immunodeficiency virus, and foreign birth in North Carolina, 1993 - 2006 - Kipp Aaron M; Stout Jason E; Hamilton Carol; Van Rie Annelies (BMC, 2008)
Abstract Background The proportion of extrapulmonary tuberculosis (EPTB) reported in the United States has been gradually increasing. HIV infection and foreign birth are increasingly associated with tuberculosis and understanding their effect on the clinical presentation of tuberculosis is important. Methods Case-control study of 6,124 persons with tuberculosis reported to the North Carolina Division of Public health from January 1, 1993 to December 31, 2006. Multivariate logistic regression was used to obtain adjusted odds ratios measuring the associations of foreign birth region and US born race/ethnicity, by HIV status, with EPTB. Results Among all patients with tuberculosis, 1,366 (22.3%) had EPTB, 563 (9.2%) were HIV co-infected, and 1,299 (21.2%) were foreign born. Among HIV negative patients, EPTB was associated with being foreign born (adjusted ORs 1.36 to 5.09, depending on region of birth) and with being US born, Black/African American (OR 1.84; 95% CI 1.42, 2.39). Among HIV infected patients, EPTB was associated with being US born, Black/African American (OR 2.60; 95% CI 1.83, 3.71) and with foreign birth in the Americas (OR 5.12; 95% CI 2.84, 9.23). Conclusion Foreign born tuberculosis cases were more likely to have EPTB than US born tuberculosis cases, even in the absence of HIV infection. Increasing proportions of foreign born and HIV-attributable tuberculosis cases in the United States will likely result in a sustained burden of EPTB. Further research is needed to explore why the occurrence and type of EPTB differs by region of birth and whether host genetic and/or bacterial variation can explain these differences in EPTB.